ANALISIS PERILAKU KONSUMEN MUSLIM KETIKA BERBELANJA DAN BERSANTAI DITEMPAT KULINER MODERN UNTUK MELAKSANAKAN IBADAH SHOLAT (STUDI PADA PLAZA DAN MALL DI KOTA PEKANBARU - Riki Hanri Malau (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
ABSTRACT The purpose of this research is to examine the leisure time of costumer behaviour at mall and plaza in Pekanbaru through perception, motivation and costumer knowledge to get pray when shalat time come. The relevant data are taken with questioner. The research population is all consumers or customers of mall and plaza, and the samples are teken from purposive convenience sampling, which taken responden easily see and fully criterion for reseach. Size of sample are 100 sample. Data analysis method used are ‘validity and reliability test of questioners, multiple regression analysis, t-test, fit-test, and classical assumption test The results show that the questioners are valid and reliable. Normality test shows residual distributed normally. Regression result are Y = 4.474+ 0.202x1 + 0.189x2 + 0.241x3 + e, means all independent variable contibuted positively to indipendent variable. F-test shows F count (11.728) >F tabel (3,090) mean Ha received dan H1 rejected, that means all variables of Perception, motivation and costumer knowledge, effect to costumer behaviour at mall and plaza in Pekanbaru. The t test result shows that Perception, motivation and costumer knowledge variable have significant positive influence for costumer behaviour at mall and plaza in to get pray when shalat time come, at mall and plaza in Pekanbaru and error standar at the 10% significant level. R test shows value 0,893 means all indipendent variable have tight relationship to dependent variabel. Fit-test shows that the model in this study has sharp, and the rersult of classical assumption test shows that there is no problem about it. Conclusion of research are all variable feasible to study but furthermore the research need to be improved for a better study.